2019
DOI: 10.1016/j.jconrel.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Targeted co-delivery of protein and drug to a tumor in vivo by sophisticated RGD-modified lipid-calcium carbonate nanoparticles

Abstract: Synchronized bio-distribution of combination therapies has several merits such as synergistic effects and reduced side-effects. Co-delivery of a protein and small molecule drug using a single nanocarrier is challenging because they possess totally different characteristics. Herein, we report the development of sophisticated nanoparticles composed of lipids, calcium carbonate and RGD peptide ligands for the co-delivery of a protein and small molecule drug combination via a simple preparation method. A 'one-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 32 publications
0
49
1
Order By: Relevance
“…To measure the release of Abraxane ® using fluorescence spectroscopy, we labeled the human serum albumin (HSA) part of the drug because it constitutes the majority of Abraxane ® (90%/10% HSA-Paclitaxel ratio). The fluorescent probe FITC is commonly used to label molecules of interests and especially albumin, which has been widely used as a model for protein delivery and is recognized as representative of the release profile of unlabeled compounds [63][64][65][66][67][68]. We assumed that the Paclitaxel-HSA bond remained stable throughout the assays since the detachment of Paclitaxel from HSA is triggered by the competition with other highly hydrophobic compounds such as fatty acids of the cell membrane [9,10,69], not present in the PBS in vitro system.…”
Section: Release Profilementioning
confidence: 99%
“…To measure the release of Abraxane ® using fluorescence spectroscopy, we labeled the human serum albumin (HSA) part of the drug because it constitutes the majority of Abraxane ® (90%/10% HSA-Paclitaxel ratio). The fluorescent probe FITC is commonly used to label molecules of interests and especially albumin, which has been widely used as a model for protein delivery and is recognized as representative of the release profile of unlabeled compounds [63][64][65][66][67][68]. We assumed that the Paclitaxel-HSA bond remained stable throughout the assays since the detachment of Paclitaxel from HSA is triggered by the competition with other highly hydrophobic compounds such as fatty acids of the cell membrane [9,10,69], not present in the PBS in vitro system.…”
Section: Release Profilementioning
confidence: 99%
“…Moreover, Seebest-PP would maximize multicolor deep imaging potency to simultaneously evaluate positional relationship of gene expression and/or lipidic carriers (such as liposomes and lipid nanoparticles) with biological structures (such as blood vessels, tissue surface and elastic fibers), oxidative stress and so on. Moreover, we have developed the quantification method of DDS carrier concentration in tissue homogenates using tissue clearing solutions [36]. We are currently optimizing the composition of Seebest-PP to determine the concentration of lipidic DDS carriers in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A highly organized nanoparticle composed of lipid, calcium carbonate, and arginylglycylaspartic acid (RGD) peptide targeting ligands was synthesized by Peng et al using a "one-step" ethanol injection method. [71] The synthesized nanoparticles exhibited the targeting ability, pH sensitivity, and synchronized biodistribution of the drugs. It was demonstrated that superoxide dismutase and paclitaxel combination had significant antitumor activity in mice.…”
Section: Calcium Mineralsmentioning
confidence: 96%